2016
DOI: 10.24220/2318-0897v24n3a2654
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in adults and older adults with Chagas disease

Abstract: The objective was to evaluate the perceived quality of life of adult and older adult patients with different clinical forms of Chagas disease. Methods This descriptive and cross-sectional research was conducted between 2005 and 2008. Data were collected from 202 patients. The World Health Organization Quality of Life-BREF was used to assess the quality of life domains. Statistical analyses included descriptive analysis, and univariate and multivariate logistic regression analyses. Results Of the 202 interviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…In a sample with several chronic forms of the disease (indeterminate, cardiac, and digestive), one study 24 showed no difference in HRQoL assessed using the WHOQOL-Bref between men and women. However, two other studies 8 , 23 that included a larger sample with the same chronic forms of the disease and used the same questionnaire showed different results. Ozaki et al 23 demonstrated that women had worse scores in the environment domain and were more likely to perceive worse HRQoL than men.…”
Section: Association Between Hrqol and Sociodemographic Or Lifestyle ...mentioning
confidence: 94%
See 2 more Smart Citations
“…In a sample with several chronic forms of the disease (indeterminate, cardiac, and digestive), one study 24 showed no difference in HRQoL assessed using the WHOQOL-Bref between men and women. However, two other studies 8 , 23 that included a larger sample with the same chronic forms of the disease and used the same questionnaire showed different results. Ozaki et al 23 demonstrated that women had worse scores in the environment domain and were more likely to perceive worse HRQoL than men.…”
Section: Association Between Hrqol and Sociodemographic Or Lifestyle ...mentioning
confidence: 94%
“…However, two other studies 8 , 23 that included a larger sample with the same chronic forms of the disease and used the same questionnaire showed different results. Ozaki et al 23 demonstrated that women had worse scores in the environment domain and were more likely to perceive worse HRQoL than men. Santos-Filho et al 8 also demonstrated that women were independently associated with worse HRQoL in the overall score as well as in the physical and psychological domains of the WHOQOL-Bref.…”
Section: Association Between Hrqol and Sociodemographic Or Lifestyle ...mentioning
confidence: 94%
See 1 more Smart Citation
“…A better female QoL was observed in studies involving patients with CD and other chronic diseases [35,44]. However, there are controversial results in that females were a predictor of worse QoL [7,9,26]. In the present study, a better perception of QoL in the Social Relations domain by women may be related to the fact that they have better social and interpersonal integration and also greater family involvement, which may favor their QoL [35], especially in this dimension.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 46%
“…Social Relations domain [9,26,27]. The lower QoL score in the Environment domain may be an impact marker of the social determinants of health on the individual perception of QoL.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%